Tensile bond strength of hydroxyethyl methacrylate dentin bonding agent on dentin surface at various drying techniques - Kun Ismiyatin (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2010)
Background: There are several dentin surface drying techniques to provide a perfect resin penetration on dentin. There are two techniques which will be compared in this study. The first technique was by rubbing dentin surface gently using cotton pellet twice, this technique is called blot dry technique. The second technique is by air blowing dentin surface for one second and continued by rubbing dentin surface gently using moist cotton. Purpose: This experiment was aimed to examine the best dentin surface drying techniques after 37% phosphoric acid etching to obtain the optimum tensile bond strength between hydroxyethyl methacrylate (HEMA) and dentin surface. Method: Bovine teeth was prepared flat to obtain the dentin surface and than was etched using 37% phosphoric acid for 15 seconds. After etching the dentin was cleaned using 20 cc plain water and dried with blot dry techniques (group I), or dried with air blow for one second (group II), or dried with air blow for one second, and continued with rubbing gently using moist cotton pellet (group III), and without any drying as control group (group IV). After these drying, the dentin surfaces were applied with resin dentin bonding agent and put into plunger facing the composite mould. The antagonist plunger was filled with composite resin. After 24 hours, therefore bond strength was measured using Autograph. Result: Data obtained was analyzed using One-Way ANOVA with 95% confidence level and continued with LSD test on p≤0.05. The result showed that the highest tensile bond strength was on group I, while the lowest on group IV. Group II and IV, III and IV, II and III did not show signigicant difference (p>0.05). Conclusion: Dentin surface drying techniques through gentle rubbing using cotton pellet twice (blot dry technique) gave the greatest tensile bond strength.Latar belakang masalah: Tehnik pengeringan permukaan dentin agar resin dapat penetrasi dengan sempurna adalah dengan cara pengusapan secara halus sebanyak dua kali menggunakan bulatan kapas, yang disebut blot dry technique, dengan semprotan udara selama 1 detik atau dengan semprotan udara selama 1 detik yang dilanjutkan dengan pengusapan secara halus menggunakan bulatan kapas basah yang diperas dan kelebihan air pada kapas diserap dengan kertas hisap. Tujuan: Penelitian ini bertujuan untuk mengetahui tehnik pengeringan permukaan dentin yang terbaik setelah etsa dengan asam phosphat 37% untuk mendapatkan kekuatan perlekatan tarik yang optimum antara HEMA dentine bonding agent dan permukaan dentin dengan menggunakan alat ukur Autograph. Metode: Permukaan dentin gigi sapi diasah rata, kemudian di etsa dengan asam phosphat 37% selama 15 detik. Permukaan dentin dicuci dengan 20 cc air dan kemudian dikeringkan dengan cara blot dry technique (kel. I), dengan semprotan udara selama 1 detik (kel. II) atau semprotan udara selama 1 detik dan dilanjutkan dengan pengusapan secara halus menggunakan bulatan kapas basah yang diperas dan kelebihan air pada kapas diserap dengan kertas hisap (kel. III) dan tanpa pengeringan permukaan dentin sebagai kontrol (kel. IV). Selanjutnya permukaan dentin diulasi dengan resin bonding dan diletakkan kedalam plunger dengan permukaan menghadap permukaan komposit. Setelah 24 jam dilakukan pengukuran kekuatan tarik dengan menggunakan alat ukur Autograph. Hasil: Analisis data menggunakan uji Anova satu arah dengan derajat kepercayaan 95% dan dilanjutkan dengan test LSD pada p≤0,05. Dari hasil penelitian didapatkan kekuatan perlekatan tarik yang paling tinggi pada kelompok I, sedangkan yang paling rendah pada kelompok IV. Didapatkan perbedaan bermakna pada kelompok I, II, III, dan IV. Pada kelompok II dan IV, III, dan IV, II, dan III tidak didapatkan perbedaan bermakna (p>0,05). Kesimpulan: Tehnik pengeringan permukaan dentin dengan cara pengusapan secara halus menggunakan bulatan kapas sebanyak 2 kali menghasilkan kekuatan perlekatan tarik terbesar.